The Khidmah Tradition of Santri Towards Kyai (The Review of ‘Urf & Psychology) - Aufa Abdillah; Erkham Maskuri (Nazhruna: Jurnal Pendidikan Islam, 2022)
The tradition of khidmah Santri to Kyai is a tradition in Pondok Pesantren that has coexisted since the beginning of the spread of Islam and is preserved up to now in the recent millennial era. Many ordinary people do not understand the tradition of khidmah Santri to Kyai and consider it such a "job as a servant". This research uses a library research approach to explain the legal basis of the santri khidmah tradition towards Kyai, and uses a descriptive qualitative approach with open-ended questionnaire techniques and categorization. The results showed that the preservation of the tradition of khidmah santri to Kyai is due to pursuing benefits both in terms of individual and social and in line with sharia form called as 'urf. The tradition of khidmah is also beneficial in terms of psychological aspects, such as resulting satisfaction and feelings of happiness and forming santri’s character likely sincerity, self-independence, respect, humility, awareness of the social environment, honesty, and responsibility. The tradition of Khidmah is also a form of santri empowerment in building a skill that brings about benefits in family life, community circle, country life, and entrepreneurship.